Working in group in project activity at English lessons in senior forms at MOBUG 2 named after I.S. Kolesnikov the town of Novokubansk - Iagodiak I. L. (Interactive science, 2022)
The article generalises group work in class project developing, refers to works of outstanding soviet psychologists and teachers dealing with personal activity of a student as the key to his achievements. The author describes effective forms of pair and group work in developing projects.
Keywords: проектно-исследовательская деятельность; групповая работа; мультимедийные презентации; project method; проектная методика; novelty; self-actualization; эгофактор; activity method; problem-solving; communicativity; ego-factor; presentations and IT- Technologies in project work; pair and group work